(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
The 2017 excavation campaign carried out in the central area of Nora by the University of Milan, allowed the discovery of a very small carnelian engraved with a crowned Victory holding a palm branch, similar to those commonly used in the Imperial age between I and III century AD. The discovery of loose gems in urban excavation is always a noteworthy event because the spot where the gem is found provides its punctual origin and an indicative chronology, moreover comparisons can be made with other museum pieces that have been already deeply studied under historical and artistic points of view. A direct comparison can be made with another Victory engraved on carnelian found in the central area of Nora in 2005, that is dated back to the second half of II century AD.